Preparation method of nano-zinc oxide composite silver ion antibacterial agent

Nanozine oxide was synthesized by the sol-gel method, and combined with the ion exchange method and liquid phase method, nanozinc oxide composite silver ion antibacterial agent was prepared, solving the agglomeration and oxidation and discoloration problems of nanozinc oxide and silver-based antibacterial agents in applications, achieving more efficient antibacterial performance and lower costs.

CN119791133AActive Publication Date: 2025-04-11ZHEJIANG UNIV

Patent Information

Application Number
CN202411675624.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-04-11
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

The existing nano zinc oxide and silver-based antibacterial agents have agglomeration problems in their applications, resulting in a decrease in antibacterial performance, and silver-based antibacterial agents are prone to oxidation and discoloration, affecting their use.

Method used

Nanozinc oxide was synthesized by sol-gel method, and silver ions were loaded into sodium zirconium phosphate by ion exchange method. Then, nanozinc oxide and sodium zirconium phosphate were combined by liquid phase method to prepare nanozinc oxide composite silver ion antibacterial agent.

Benefits of technology

The agglomeration of nano zinc oxide is reduced through the composite process, the antibacterial performance is improved, and the cost is reduced due to the reduction of silver use. At the same time, due to the differences in the antibacterial mechanisms of zinc oxide and silver ions, the composite antibacterial agent has better antibacterial properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119791133A_ABST
    Figure CN119791133A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of antibacterial agents, and particularly relates to a preparation method of a nano-zinc oxide composite silver ion antibacterial agent, which comprises the following steps: 1, synthesizing nano-zinc oxide by a sol-gel method; 2, loading silver ions to the sodium zirconium phosphate by adopting an ion exchange method to obtain silver-loaded sodium zirconium phosphate; and 3, compounding the nano-zinc oxide and the silver-loaded sodium zirconium phosphate by adopting a liquid phase method to obtain the nano-zinc oxide composite silver ion antibacterial agent. According to the invention, the antibacterial mechanisms of zinc oxide and silver ions are different, and a synergistic antibacterial mechanism exists when zinc oxide and silver ions are compounded, so that the obtained composite antibacterial agent has more excellent antibacterial performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of antibacterial agents, and specifically relates to a method for preparing a nano zinc oxide composite silver ion antibacterial agent. Background Art

[0002] Antimicrobial agents are a class of agents used to prevent and treat pathogenic microorganisms such as bacteria and fungi. Antimicrobial agents can be divided into natural antimicrobial agents and artificial antimicrobial agents according to their sources. Natural antimicrobial agents have the advantages of safety, non-toxicity, and broad-spectrum bactericidal properties, but they cannot be processed secondary, and their production capacity is low due to resource constraints, so their actual applications are very limited. Artificial antimicrobial agents can be divided into organic antimicrobial agents and inorganic antimicrobial agents according to their ingredients. Organic antimicrobial agents can effectively inhibit the growth and reproduction of pathogenic microorganisms and have the characteristics of rapid effectiveness, but they have problems such as poor thermal stability and chemical stability, safety risks, etc., and their application range is narrow, and they are gradually facing elimination. Inorganic antimicrobial agents are a class of antimicrobial agents made by using the bactericidal or antibacterial ability of metals such as silver, zinc, copper, and titanium and their ions. Inorganic antimicrobial agents have the advantages of broad-spectrum antimicrobial, safety, non-toxicity, good stability, and easy production and processing. They are more adaptable to the application of actual production and life, and can be used to improve and maintain the antimicrobial properties of daily necessities such as fabrics, plastics, and rubber for a long time. They are gradually becoming a research hotspot in the field of antimicrobial agents.

[0003] At present, the common inorganic antibacterial agents on the market mainly include nano zinc oxide, silver-based antibacterial agents, etc.

[0004] Nano zinc oxide can produce a variety of active oxygen substances, leading to denaturation of cell membranes, proteins, and plasmids of pathogenic microorganisms, lipid peroxidation, and at the same time destroying mitochondrial groups, inducing necrosis of pathogenic microorganisms, with significant bactericidal effects. It also has the advantages of safety and non-toxicity, high specific surface area, multiple reaction sites, and low price. It can be synthesized by various physical and chemical methods such as solid phase method, liquid phase method, and gas phase method. However, nano zinc oxide, as a nano powder, is very easy to agglomerate, and agglomeration leads to the presence of micron-sized particles in the powder. These agglomerates will not only lead to a decrease in the antibacterial properties of the antibacterial agent, but also affect the doping and dispersion of the antibacterial agent in fabrics, plastics, rubber and other products, resulting in these antibacterial products. Problems such as color difference and decreased mechanical strength.

[0005] Silver-based antimicrobial agents can release silver ions, which can destroy the cell walls of pathogenic microorganisms, inhibit their respiration, and destroy their DNA, thereby killing pathogenic microorganisms. Silver-based antimicrobial agents can be divided into loaded and unloaded types according to whether silver is loaded on other carriers. The silver-based antimicrobial agents used in the early stage were mainly unloaded types, including nanosilver particles, nanosilver sols, silver ion solutions, etc. The concentration of silver ions produced by unloaded silver-based antimicrobial agents was high, the bactericidal effect was significant, and the effect was fast. The bactericidal effect or the antibacterial property of various daily necessities can be achieved in a short time, but because silver is an active metal with poor stability, silver or silver ions are easily oxidized, especially under the action of ultraviolet light, the aggravated oxidation of silver will cause the antibacterial property of daily necessities to drop sharply and discolor at the same time, affecting the use. In addition, silver is also prone to react with elements such as phosphorus and sulfur to produce discoloration, and the production and use of daily necessities such as plastics and rubber inevitably involve sulfur elements. The problem of unloaded silver-based antimicrobial agents being easily oxidized and discolored seriously limits their application in various daily necessities. In order to solve this problem, industry researchers have tried to load silver or silver ions into carriers such as zeolite, silica gel, and sodium zirconium hydroxyphosphate to avoid silver oxidation and reaction with elements such as phosphorus and sulfur. At the same time, it can precipitate or dissolve from the carrier during use, which also achieves the antibacterial effect. The precipitation of silver in the loaded silver antibacterial agent is a slow and long-term process, which has a sustained release effect, effectively ensuring that daily products have long-term antibacterial properties. Compared with carriers such as zeolite and silica gel, the silver loaded by sodium zirconium hydroxyphosphate is more stable. Therefore, silver-loaded sodium zirconium phosphate is currently the most commonly used and most studied type of loaded silver ion antibacterial agent. Of course, loaded silver ion antibacterial agents such as sodium zirconium hydroxyphosphate also have some problems, such as insufficient silver ion loading resulting in insufficient bactericidal effect, and silver as a precious metal indirectly leading to the high price of silver-based antibacterial agents.

[0006] The invention of CN114957734A "Preparation method and application of an antibacterial agent and a composite material containing the same" states: 100 parts by weight of thermoplastic elastomer material, 5-30 parts by weight of porous material-loaded guanidine salt antibacterial agent, 50-200 parts by weight of filler oil, 5-30 parts by weight of silver-loaded sodium zirconium phosphate antibacterial agent and / or 10-60 parts by weight of nano zinc oxide are plasticized evenly and then screw extruded and granulated to obtain a composite antibacterial masterbatch. Summary of the invention

[0007] The problem to be solved by the present invention is to provide a method for preparing a nano zinc oxide composite silver ion antibacterial agent with good antibacterial performance.

[0008] In order to solve the above problems, the present invention provides a method for preparing a nano zinc oxide composite silver ion antibacterial agent, comprising the following steps:

[0009] 1. Synthesize nano zinc oxide using sol-gel method;

[0010] 2. Using an ion exchange method to load silver ions onto sodium zirconium phosphate to obtain silver-loaded sodium zirconium phosphate;

[0011] 3. Nano zinc oxide and silver-loaded sodium zirconium phosphate are compounded by a liquid phase method to obtain a nano zinc oxide composite silver ion antibacterial agent.

[0012] As an improvement of the preparation method of the nano zinc oxide composite silver ion antibacterial agent of the present invention, the step 1 comprises the following steps:

[0013] 1.1) preparing an ethanol aqueous solution with an ethanol mass fraction of 80% to 95%, and dividing it into two equal parts; adding zinc acetate to one of the ethanol aqueous solutions to obtain a zinc acetate alcohol aqueous solution with a zinc acetate mass fraction of 2% to 4% (preferably 3%); adding sodium hydroxide to the other ethanol aqueous solution to obtain a sodium hydroxide alcohol aqueous solution with a sodium hydroxide mass fraction of 0.5% to 1% (preferably 0.75%);

[0014] At 0-30° C. (preferably 20-30° C.) and under stirring conditions, the sodium hydroxide alcohol aqueous solution is added dropwise to the zinc acetate alcohol aqueous solution for 5-10 minutes. After the addition is completed, the mixture is stirred for 5-10 minutes at a temperature of 0-30° C., and then kept warm and allowed to stand for 20-40 minutes (for example, 30 minutes).

[0015] 1.2) Add water to the product obtained in step 1.1) and shake well, then centrifuge to obtain precipitate I, wash precipitate I by centrifugation with water (2 to 3 times); then dry (dry in a vacuum oven at 60±10°C until constant weight) to obtain nano zinc oxide powder.

[0016] Note: The amount of water used for shaking well is about 2 to 3 times the sum of the volumes of 2 equal parts of ethanol-water solution.

[0017] As a further improvement of the preparation method of the nano zinc oxide composite silver ion antibacterial agent of the present invention, the step 2 comprises the following steps:

[0018] 2.1) dispersing sodium zirconium hydroxyphosphate in deionized water to obtain a carrier suspension, wherein the mass fraction of sodium zirconium hydroxyphosphate in the carrier suspension is 2.5% to 5% (preferably 3% to 4.5%); dissolving silver nitrate in deionized water to obtain a silver source solution, wherein the mass fraction of silver nitrate in the silver source solution is 1% to 1.5%;

[0019] First, the carrier suspension and the silver source solution are mixed in a volume ratio of 1:2-4 (preferably 1:3-4), and then the pH is adjusted to 3-4, and stirred at 40±10° C. for 4-6 hours;

[0020] 2.2) Add water to the product obtained in step 2.1) and shake well, then centrifuge to obtain precipitate II; wash precipitate II by centrifugation with water (2 to 3 times); then dry (dry in a vacuum oven at 60±10°C until constant weight) to obtain white powder A;

[0021] Note: The amount of water involved in adding water and shaking is about 2 to 3 times the mass of the product obtained in step 2.1);

[0022] 2.3) Substituting white powder A for sodium zirconium hydroxyphosphate, repeating the above steps 2.1) to 2.2) to obtain white powder B;

[0023] 2.4) Calcine the white powder B at a temperature of 700 to 900° C. (preferably 800° C.) for 2 to 3 h to obtain silver-loaded sodium zirconium phosphate powder.

[0024] As a further improvement of the preparation method of the nano zinc oxide composite silver ion antibacterial agent of the present invention, the step three comprises the following steps:

[0025] 3.1) Dispersing the nano zinc oxide powder obtained in step 1 in deionized water, adding an activator and a surfactant, stirring for 3 to 5 minutes, and then adding the silver-loaded sodium zirconium phosphate powder obtained in step 2, and continuing to stir for 30 to 60 minutes to obtain a mixed solution;

[0026] In the mixed solution, the mass fraction of nano zinc oxide is 1% to 3% (preferably 2 to 3%), the mass fraction of silver-loaded sodium zirconium phosphate is 1%, the mass fraction of surfactant is 0.1% to 0.5% (preferably 0.3% to 0.4%), and the mass fraction of activator is 0.1% to 0.5% (preferably 0.2% to 0.4%);

[0027] 3.2) The mixed solution obtained in step 3.1) was filtered, and the obtained precipitate was dried (dried in a vacuum oven at 60±10° C. until constant weight) to obtain a white powder C;

[0028] 3.3) The white powder C obtained in step 3.2) is calcined (calcined to remove the surfactant and activator), the calcination temperature is 600±50° C., and the time is 3±0.5 h to obtain a nano zinc oxide composite silver ion antibacterial agent.

[0029] As a further improvement of the preparation method of the nano zinc oxide composite silver ion antibacterial agent of the present invention, in step 2.1), the sodium zirconium hydroxyphosphate is a cubic crystal of 1-3 μm (sodium zirconium hydroxyphosphate cubic crystal powder); and citric acid is used to adjust the pH.

[0030] As a further improvement of the preparation method of the nano zinc oxide composite silver ion antibacterial agent of the present invention, in step 3.1), the surfactant is sodium dodecyl sulfate or sodium dodecylbenzene sulfonate, and the activator is stearic acid.

[0031] The invention also provides a nano zinc oxide composite silver ion antibacterial agent prepared according to the preparation method.

[0032] Compared with the prior art, the technical advantages of the present invention are:

[0033] 1. Silver ions were loaded into sodium zirconium hydroxyphosphate carrier by ion exchange method to obtain silver-loaded sodium zirconium phosphate powder, and the silver loading capacity was increased by optimizing the loading process and multiple ion exchanges.

[0034] 2. Nano zinc oxide and silver-loaded sodium zirconium phosphate are compounded by a liquid phase method, so that the nano zinc oxide particles can be more evenly compounded on the surface of the silver-loaded sodium zirconium phosphate cubic crystal, reducing the agglomeration of nano zinc oxide.

[0035] 3. Nano zinc oxide and silver-loaded sodium zirconium phosphate are compounded to prepare nano zinc oxide composite silver ion antibacterial agent, which reduces the use of silver-based antibacterial agents and reduces costs. At the same time, due to the differences in the antibacterial mechanisms of zinc oxide and silver ions, the combined use has a synergistic antibacterial mechanism, and the composite antibacterial agent has better antibacterial properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The specific embodiments of the present invention are further described in detail below with reference to the accompanying drawings.

[0037] Figure 1 This is a SEM photo of the nano zinc oxide composite silver ion antibacterial agent prepared in Example 1;

[0038] Figure 1 In the figure, the left picture was taken at 2500 times magnification, and the right picture was taken at 10000 times magnification.

[0039] Figure 2 This is an EDS photo of the nano zinc oxide composite silver ion antibacterial agent prepared in Example 1;

[0040] They respectively reflect the distribution of six elements, namely Zr, P, Zn, Na, O and Ag, in the antibacterial agent. The EDS layered image is the superposition result of the distribution of the above six elements, indicating that the six elements are evenly distributed in the antibacterial agent.

[0041] Figure 3 This is the XRD spectrum of the nano zinc oxide composite silver ion antibacterial agent prepared in Example 1. DETAILED DESCRIPTION

[0042] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0043] Embodiment 1, a method for preparing a nano zinc oxide composite silver ion antibacterial agent, sequentially performing the following three steps:

[0044] 1. Synthesizing high-purity nano zinc oxide by sol-gel method, including the following steps:

[0045] 1.1) Prepare 80% (mass %) ethanol aqueous solution and divide it into 2 equal parts;

[0046] Add zinc acetate to one of the ethanol aqueous solutions to obtain a zinc acetate alcohol aqueous solution with a zinc acetate mass fraction of 3%; add sodium hydroxide to the other ethanol aqueous solution to obtain a sodium hydroxide alcohol aqueous solution with a sodium hydroxide mass fraction of 0.75%;

[0047] At 25°C with stirring, add the above sodium hydroxide alcohol aqueous solution dropwise to the zinc acetate alcohol aqueous solution for 10 minutes, and keep stirring at 25°C for 5 minutes. After stirring, keep it at 25°C and let it stand for 30 minutes.

[0048] 1.2) Add water to the product obtained in step 1.1) and shake well (the amount of water used is about twice the sum of the volumes of the two equal parts of ethanol-water solution), centrifuge to obtain a precipitate, and continue to centrifuge and wash the precipitate twice with water (until the eluent is neutral).

[0049] The washed precipitate was placed in a vacuum oven at 60°C and dried until constant weight was obtained to obtain nano zinc oxide powder.

[0050] Second, the silver ions are loaded into sodium zirconium phosphate by ion exchange method, comprising the following steps:

[0051] 2.1) Dispersing sodium zirconium hydroxyphosphate cubic crystal powder with a particle size of 1-3 μm in deionized water to obtain a carrier suspension, wherein the mass fraction of sodium zirconium hydroxyphosphate in the carrier suspension is 4.5%; dissolving silver nitrate in deionized water to obtain a silver source solution, wherein the mass fraction of silver nitrate in the silver source solution is 1.5%.

[0052] The carrier suspension and the silver source solution were mixed in a volume ratio of 1:4, and an appropriate amount of citric acid was added to adjust the pH to 3.5, and the mixture was stirred and reacted at 40° C. for 5 hours.

[0053] 2.2) Add water to the product obtained in step 2.1) (the amount of water used is about twice that of the product obtained in step 2.1)), shake well, and centrifuge to obtain a precipitate. Continue to centrifuge and wash the precipitate with water twice (until the eluent is neutral). Then place it in a vacuum oven at 60°C and dry it until it is dry to obtain a white powder A.

[0054] 2.3) Repeat steps 2.1) to 2.2) once with white powder A replacing the cubic crystal powder of sodium zirconium hydroxyphosphate to obtain white powder B.

[0055] 2.4) The white powder B was calcined at 800°C for 2 h to obtain silver-loaded sodium zirconium phosphate powder.

[0056] 3. Compounding nano zinc oxide and silver-loaded sodium zirconium phosphate by liquid phase method, including the following steps:

[0057] 3.1) Disperse the nano zinc oxide powder obtained in step 1 in deionized water, add an activator and a surfactant, stir for 5 minutes, then add the silver-loaded sodium zirconium phosphate powder obtained in step 2, and continue stirring for 45 minutes to obtain a mixed solution;

[0058] In the mixed solution, the mass fraction of nano zinc oxide is 2%, the mass fraction of silver-loaded sodium zirconium phosphate is 1%, the mass fraction of surfactant is 0.3%, and the mass fraction of activator is 0.2%;

[0059] The surfactant is sodium lauryl sulfate and the activator is stearic acid.

[0060] 3.2) The mixed solution obtained in step 3.1) was filtered to obtain a precipitate, and the precipitate was dried in a vacuum oven at 60° C. until constant weight was obtained to obtain a white powder.

[0061] 3.3) The white powder obtained in step 3.2) was calcined at a temperature of 600° C. for 3 h to obtain a nano zinc oxide composite silver ion antibacterial agent.

[0062] Example 1 A nano zinc oxide composite silver ion antibacterial agent was synthesized. The composition structure of the nano zinc oxide composite silver ion antibacterial agent was characterized by SEM, EDS and XRD. The equipment used for SEM and EDS testing was a Hitachi SU8010 field emission scanning electron microscope, and the equipment used for XRD testing was a PANalytical X'Pert PRO MPD X-ray powder diffractometer from the Netherlands. SEM photo ( Figure 1 ) shows that nano zinc oxide is evenly compounded on the surface of sodium zirconium phosphate silver cubic crystals with a size of 1-3μm. EDS photo ( Figure 2 ) shows that the antibacterial agent contains Zr, P, Zn, Na, O, Ag and other elements and is evenly distributed. XRD spectrum ( Figure 3 ) showed the presence of crystalline phases of sodium zirconium phosphate and zinc oxide in the antibacterial agent sample.

[0063] Example 2: A method for preparing a nano zinc oxide composite silver ion antibacterial agent, with the following changes compared to Example 1:

[0064] In step 2.1), the mass fraction of sodium zirconium hydroxyphosphate in the carrier suspension was changed from 4.5% to 3%; the mass fraction of silver nitrate in the silver source solution was changed from 1.5% to 1%, and the stirring reaction time was changed from 5h to 4h;

[0065] The rest is the same as Example 1.

[0066] Example 3: A method for preparing a nano zinc oxide composite silver ion antibacterial agent, with the following changes relative to Example 1:

[0067] In step 2.1), the volume ratio of the carrier suspension and the silver source solution was changed from 1:4 to 1:3, and the stirring reaction time was changed from 5 h to 6 h.

[0068] The rest is the same as Example 1.

[0069] Example 4: A method for preparing a nano zinc oxide composite silver ion antibacterial agent, with the following changes relative to Example 1:

[0070] In the mixed solution of step 3.1), the mass fraction of nano zinc oxide was changed from 2% to 3%, the mass fraction of surfactant was changed from 0.3% to 0.4%, and the mass fraction of activator was changed from 0.2% to 0.3%.

[0071] The rest is the same as Example 1.

[0072] Example 5: A method for preparing a nano zinc oxide composite silver ion antibacterial agent, with the following changes relative to Example 1:

[0073] In the mixed solution of step 3.1), the surfactant is changed from sodium dodecyl sulfate to sodium dodecylbenzene sulfonate, and the mass fraction of the surfactant is changed from 0.3% to 0.4%.

[0074] The rest is the same as Example 1.

[0075] Comparative Example 1: The following changes were made relative to Example 1:

[0076] In step 2.1), the volume ratio of the carrier suspension and the silver source solution was changed from 1:4 to 1:1; the rest was the same as in Example 1.

[0077] Comparative Example 2: The following changes were made relative to Example 1:

[0078] In step 2.1), the mass fraction of silver nitrate in the silver source solution was changed from 1.5% to 0.5%; the rest was the same as in Example 1.

[0079] Comparative Example 3: The following changes were made relative to Example 1:

[0080] In step 2.1), the reaction time was changed from 5 h to 2 h; the rest was the same as in Example 1.

[0081] Comparative Example 4: The following changes were made relative to Example 1:

[0082] The repeated treatment of step 2.3) was cancelled, and the white powder A obtained in step 2.2) was directly calcined in step 2.4), and the rest was the same as in Example 1.

[0083] Comparative Example 5: The following changes were made relative to Example 1:

[0084] The use of the surfactant in step 3.1) is eliminated, that is, the mass fraction of the surfactant is 0%, and the rest is the same as in Example 1.

[0085] Comparative Example 6: The following changes were made relative to Example 1:

[0086] Change step 3 to solid phase mixing method:

[0087] The nano zinc oxide powder and the silver-loaded sodium zirconium phosphate powder were successively added into a dry mixer, and the composite antibacterial agent was obtained after stirring and mixing for 60 minutes. The mass ratio of the nano zinc oxide and the silver-loaded sodium zirconium phosphate powder was still 2:1.

[0088] The rest is the same as Example 1.

[0089] Comparative Example 7: Only the nano zinc oxide powder obtained in step 1 of Example 1 was used as an antibacterial agent.

[0090] Comparative Example 8: Only the silver-loaded sodium zirconium phosphate powder obtained in step 2 of Example 1 was used as an antibacterial agent.

[0091] Comparative Example 9: The calcination treatment in step 3.3) was omitted, that is, the white powder obtained in step 3.2) was directly used as an antibacterial agent. The rest was the same as in Example 1.

[0092] In order to reflect the technical advantages of the ion exchange process used in step 2 of the present invention, the antibacterial agents prepared in Example 1, Example 2, Example 3, and Comparative Examples 1-4 were subjected to EDS test comparison, the mass fractions of the Ag element and the Na element were compared, and the ratio of the number of Ag atoms to the sum of the numbers of Na and Ag atoms was defined as the Ag loading amount. The results are shown in Table 1.

[0093] Table 1

[0094] Serial number Na mass fraction wt% Ag mass fraction wt% Ag loading Example 1 5.19% 1.23% 4.80% Example 2 5.23% 1.23% 4.77% Example 3 5.22% 1.23% 4.78% Comparative Example 1 5.95% 0.53% 1.86% Comparative Example 2 5.83% 0.57% 2.04% Comparative Example 3 6.13% 0.27% 0.93% Comparative Example 4 5.53% 0.86% 3.21%

[0095] Taking Example 1 as an example, after conversion, the number of Ag atoms is 1.23 / 108=0.0114, and the number of Na atoms is 0.2257. Therefore, the Ag loading is 0.0114 / (0.0114+0.2257)=4.80%.

[0096] In order to reflect the antibacterial performance advantages of the nano zinc oxide composite silver ion antibacterial agent prepared by the present invention, the antibacterial agents of Examples 1-5 and Comparative Examples 1-9 were respectively added to the same liquid silicone rubber (liquid silicone rubber of Zhejiang Zhongtian Oriental Fluorosilicone Materials Co., Ltd.) to prepare antibacterial silicone rubber samples, and the amount of antibacterial agent added was 1.2% (mass%). 12 pieces of 5cm*5cm*0.2cm samples were cut from each sample for the antibacterial rate test of Escherichia coli and Staphylococcus aureus. The antibacterial rate test was performed in accordance with the national standard WS / T 650-2019. The antibacterial rates of all antibacterial silicone rubber samples against two pathogenic microorganisms are shown in Table 2. After the antibacterial agents prepared in Examples 1-5 were added to silicone rubber, the antibacterial rates of silicone rubber against Escherichia coli and Staphylococcus aureus exceeded 90% and 99%, respectively. The Ag loading of the antibacterial agents in Comparative Examples 1 to 4 decreased, and the antibacterial effect of the antibacterial agents decreased significantly. In the antibacterial agents of Comparative Examples 5 and 6, nano zinc oxide and silver-loaded sodium zirconium phosphate were not composited uniformly, resulting in a decrease in the antibacterial effect of the composite antibacterial agent. Comparative Examples 7 and 8 only used nano zinc oxide and silver-loaded sodium zirconium phosphate, respectively, and their antibacterial effects were not as good as the composite antibacterial agent of the present invention. Comparative Example 9 did not calcine to remove the surfactant, and the antibacterial effect decreased due to the decrease in the proportion of effective antibacterial components in the composite antibacterial agent.

[0097] Table 2

[0098] Antibacterial rate (Escherichia coli) Inhibition rate (Staphylococcus aureus) Example 1 91.2% 99.9% Example 2 90.9% 99.8% Example 3 91.0% 99.8% Example 4 91.1% 99.9% Example 5 91.2% 99.9% Comparative Example 1 64.3% 70.5% Comparative Example 2 68.0% 76.7% Comparative Example 3 49.3% 54.9% Comparative Example 4 79.1% 88.4% Comparative Example 5 86.7% 95.2% Comparative Example 6 80.1% 89.0% Comparative Example 7 78.8% 87.5% Comparative Example 8 89.6% 99.0% Comparative Example 9 89.5% 96.1%

[0099] Finally, it should be noted that the above examples are only some specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and there are many variations. All variations that can be directly derived or associated with the content disclosed by a person skilled in the art should be considered as the protection scope of the present invention.

Claims

1. A method for preparing a nano zinc oxide composite silver ion antibacterial agent, characterized in that The following steps are involved:

1. Synthesize nano zinc oxide using sol-gel method; 2. Using an ion exchange method to load silver ions onto sodium zirconium phosphate to obtain silver-loaded sodium zirconium phosphate; 3. Nano zinc oxide and silver-loaded sodium zirconium phosphate are compounded by a liquid phase method to obtain a nano zinc oxide composite silver ion antibacterial agent.

2. The method for preparing the nano zinc oxide composite silver ion antibacterial agent according to claim 1, characterized in that: The step 1 comprises the following steps: 1.1) preparing an ethanol aqueous solution with an ethanol mass fraction of 80% to 95%, and dividing it into two equal parts; adding zinc acetate to one of the ethanol aqueous solutions to obtain a zinc acetate alcohol aqueous solution with a zinc acetate mass fraction of 2% to 4%; adding sodium hydroxide to the other ethanol aqueous solution to obtain a sodium hydroxide alcohol aqueous solution with a sodium hydroxide mass fraction of 0.5% to 1%; At 0-30°C and under stirring conditions, add the sodium hydroxide alcohol solution dropwise to the zinc acetate alcohol solution for 5-10 minutes. After the addition is complete, continue to keep warm and stir for 5-10 minutes, and then keep warm and stand for 20-40 minutes. 1.2) Add water to the product obtained in step 1.1) and shake well, then centrifuge to obtain precipitate I, wash precipitate I by centrifugation with water, and then dry to obtain nano zinc oxide powder.

3. The method for preparing the nano zinc oxide composite silver ion antibacterial agent according to claim 1 or 2, characterized in that: The step 2 comprises the following steps: 2.1) dispersing sodium zirconium hydroxyphosphate in deionized water to obtain a carrier suspension, wherein the mass fraction of sodium zirconium hydroxyphosphate in the carrier suspension is 2.5% to 5%; dissolving silver nitrate in deionized water to obtain a silver source solution, wherein the mass fraction of silver nitrate in the silver source solution is 1% to 1.5%; First, the carrier suspension and the silver source solution are mixed in a volume ratio of 1:2-4, and then the pH is adjusted to 3-4, and stirred at 40±10°C for 4-6 hours; 2.2) Add water to the product obtained in step 2.1) and shake well, then centrifuge to obtain precipitate II; wash precipitate II by centrifugation with water; then dry to obtain white powder A; 2.3) Substituting white powder A for sodium zirconium hydroxyphosphate, repeating the above steps 2.1) to 2.2) to obtain white powder B; 2.4) The white powder B is calcined at a temperature of 700 to 900° C. for 2 to 3 h to obtain silver-loaded sodium zirconium phosphate powder.

4. The method for preparing the nano zinc oxide composite silver ion antibacterial agent according to claim 3, characterized in that: The step three includes the following steps 3.1) Dispersing the nano zinc oxide powder obtained in step 1 in deionized water, adding an activator and a surfactant, stirring for 3 to 5 minutes, and then adding the silver-loaded sodium zirconium phosphate powder obtained in step 2, and continuing to stir for 30 to 60 minutes to obtain a mixed solution; In the mixed solution, the mass fraction of nano zinc oxide is 1% to 3%, the mass fraction of silver-loaded sodium zirconium phosphate is 1%, the mass fraction of surfactant is 0.1% to 0.5%, and the mass fraction of activator is 0.1% to 0.5%; 3.2) The mixed solution obtained in step 3.1) is filtered and the obtained precipitate is dried to obtain a white powder C; 3.3) The white powder C obtained in step 3.2) is calcined at a temperature of 600±50° C. for 3±0.5 h to obtain a nano zinc oxide composite silver ion antibacterial agent.

5. The method for preparing the nano zinc oxide composite silver ion antibacterial agent according to claim 4, characterized in that: In step 2.1), sodium zirconium hydroxyphosphate is in the form of cubic crystals of 1-3 μm; and pH is adjusted using citric acid.

6. The method for preparing the nano zinc oxide composite silver ion antibacterial agent according to claim 5, characterized in that: In step 3.1), the surfactant is sodium dodecyl sulfate or sodium dodecylbenzene sulfonate, and the activator is stearic acid.

Citation Information

Patent Citations

  • Natural macromolecule / inorganic nanometer antibacterial composite material and preparation method thereof

    CN103881150A

  • Ag, Cu and Zn doped nanometer titanium dioxide composite antibacterial agent and preparation method thereof

    CN104045853A

  • Nano-zinc protective silver ion-containing inorganic antibacterial powder and preparation method

    CN104170820A

  • Nano zinc oxide / silver composite antibacterial agent and preparation method thereof

    CN107142718A

  • Preparation method of ZnO nanorod-loaded nano-Ag complex antimicrobial agent

    CN109221249A

Cited By

  • Method for preparing nano ZnO / silver-loaded zirconium phosphate composite antibacterial agent through self-assembly

    CN121647277A